Kajian Hukum Islam tentang Rekening Bersama (RekBer) pada E-Commerce - Mursid, Fadillah; Nurhisam, Luqman (TAWAZUN: Journal of Sharia Economic Law, 2022)
In trading conducted online or better known as E-Commerce, there are many cases of fraud that occur. Until finally, a Joint account emerged as an alternative for safe online transactions. Based on the above background, this study aims to discuss the legal status of the use of joint account services and any contracts that can be used in Joint Account transactions (RekBer) in E-Commerce. This research is a normative legal research, while the specification of this research is analytical descriptive. The main approach taken is doctrinal. The results of this study are that in Islamic law the use of third party services in a legal transaction is permissible (permissible), while contracts in account transactions in E-Commerce can use a combination of salam contracts and wakalah bil ujrah or ijaroh a'mal contracts.